PLS Analysis: How Family Support Affect Students' Self-Confidence in Completing Thesis - Arya Fendha Ibnu Shina (Universitas Bumigora, 2023)
A student's success can not be separated from a final project called a thesis as a determinant of student graduation in college. However, in the process, students often face various obstacles and challenges. To overcome this, students need to have high self-confidence. In increasing self-confidence, the role of the family is required as the main factor that encourages students to succeed. The purpose of this paper is to determine the influence of forms of family support in the form of informational support, instrumental support, appraisal and reward support, and emotional support on the self-confidence of 58 students of the Islamic Guidance and Counseling Study Program class of 2018 UIN Sunan Kalijaga Yogyakarta who are working on a thesis for students. The data analysis method used is Partial Least Square (PLS). Partial Least Square (PLS) is a component or variant-based Structural Equation Model (SEM) model. Partial Least Square (PLS) is a variant-based Structural Equation Model (SEM) model.The results of this study state that 46.7% of students' self-confidence variations in completing a thesis are influenced by family support while the rest is influenced by other factors. In addition, emotional support has a significant effect on student self-confidence in doing a thesis with a p-value of 0.000. Thus, it can be concluded that emotional support becoming the form of family support that played the most important role in increasing student self-confidence. The results of this study will later be used as suggestion for students’s family and also for counselors in modifying behavior to increase students’s self-confidence.